2017
DOI: 10.1111/ijlh.12681
|View full text |Cite
|
Sign up to set email alerts
|

Critical values in hematology of 862 institutions in China

Abstract: There exists a wide variety for critical value reporting in hematology in China. Laboratories should establish a policy of critical value reporting suited for their own situations and consult with clinicians to set critical value lists. Critical values are generally reported in a timely manner in China, but some measures should be taken to further improve the timeliness of critical value reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Some domestic publications have addressed that the categories of critical values were basically consistent in different medical institutions. Nevertheless, there are significant differences in the critical value thresholds [Zeng 2013;Ye 2017]. Although previous studies have set critical value thresholds by considering the ages and diseases of relevant patients through analyzing big data of laboratory results, there is a lack of making corresponding clinical evaluation [Du 2018;Tan 2019].…”
Section: Discussionmentioning
confidence: 99%
“…Some domestic publications have addressed that the categories of critical values were basically consistent in different medical institutions. Nevertheless, there are significant differences in the critical value thresholds [Zeng 2013;Ye 2017]. Although previous studies have set critical value thresholds by considering the ages and diseases of relevant patients through analyzing big data of laboratory results, there is a lack of making corresponding clinical evaluation [Du 2018;Tan 2019].…”
Section: Discussionmentioning
confidence: 99%
“…The TATs function as a quality indicator for CR re por tin g (4,8). The TATs of CR me asu reme nt, identification, verification, and reporting in the outpatient and emergency departments were shorter than those in the inpatient department, which might be related to the work pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, some regional investigations of CR polices and several standards, guidelines and expert consensuses on CR exist (1,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). These promote the standardization and consensuses of CR policies (18,19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 92% of responses indicated that laboratory staff are trained in reporting critical values, that is, the staff are familiar with the critical value limits and how to notify when these are breached [27]. According to Ye et al [28], training programmes to improve delivery of critical values between relevant personnel should be undertaken. Our study found that delays in critical value reporting were significantly different between physicians and technicians, which might be due to policies and the guidelines not being followed.…”
Section: Correct Answers Of Upper and Lower Limits And Units Of Criti...mentioning
confidence: 99%